On the Generalized Solution of the Boundary-Value Problem for the Operator-Differential Equations of the Second Order with Variable Coefficients - Aliev, A. R. (Журнал математичної фізики, аналізу, геометрії, 2006)
Boundary-value problem for a class of operator-differential equations of the second order with variable coefficients on $[0;\infty )$ is studied. The principal part of investigated operator-differential equation has discontinuities. Sufficient conditions for the existence and uniqueness of generalized solutions of the boundary-value problem for such equations are given. These conditions are expressed only in terms of coefficients of the operator-differential equation. Mathematics Subject Classification: 47E05, 34B40.